Rational Pharmacological Prophylaxis of Gestation Process Complications in Pregnant Women with Varicose Disease - Markin L.; Shatylovytch K. (Львівський клінічний вісник)
Introduction. The pathological changes of the venous system in pregnant women and the mothers are manifested in the occurrence of varicose veins of the lower extremities, venous thrombosis and thromboembolism. Varicose veins of the lower extremities are observed in 20.0-40.0% of pregnant women, in more than 70.0 % of women, manifestation of this disease occurs in the third trimester of the gestational process. The structural changes and a further decrease in the elasticity of the walls of the venous vessels are systemic, but the most affected are the veins that are least covered by muscles – the surface veins of the lower limbs, rectum, small pelvis, and also the fetoplacental complex. Actually, one of the gestating complications of chronic venous insufficiency is the formation of secondary placental dysfunction with clinical implementation in the form of fetal distress, fetal growth retardation syndrome (FGRS), preeclampsia (PE). Aim. To evaluate the effectiveness of the treatment of varicose veins of the lower extremities and prevention of its gestational complications using venotonic drug Normoven. Materials and methods. There were examined 60 women aged 21-45 (gestational age 28 weeks or more) who suffered from the varicose veins of the lower extremities. In all patients, the severity of the disease corresponded to the clinical class C1-C3 according to the international classification (CEAР). Observations included the all standard clinical and laboratory examination, antenatal cardiotocography (after 30 weeks), determination of fetal biophysical profile (BPP), and ultrasound doplerometric examination determining the state of blood flow in the arteries of the uterus, placental bed (spiral artery (SA)), umbilical (UA) and middle cerebral artery (MCA), renal artery (RA), venous duct (VD)). The effectiveness of the proposed treatment was evaluated by measuring the diameter of the lower leg at the ankles once a week and subjectively. Were evaluated the following symptoms: pain and feeling of heaviness in the lower extremities at the end of the day, reduced tolerance to static loads, and the presence of a vessel in the fluid muscle. Results. The first, yet preclinical, response of the mother-placenta-fetal system to any disease of the maternal organism is the violation of hemodynamics in its utero-placental contour.